How Does the Entrepreneurship Education Influence the Students’ Innovation? Testing on the Multiple Mediation Model - Wei, Xingjian; Liu, Xiaolang; Sha, Jian (Frontiers in Psychology, 2019)
This study aims to explore the multiple mediating effects of political skills and entrepreneurial opportunity recognition between perceived entrepreneurship education and innovation. Structural equation is used to analyze data collected from 269 Chinese student entrepreneurs. Results showed that (1) There is a positive relationship between perceptions of entrepreneurship education and perceptions of innovation, (2) political skills and entrepreneurial opportunity recognition separately play a mediating role between perceived entrepreneurship education and innovation, and (3) political skills and entrepreneurial opportunity recognition play a chain mediating effect between perceived entrepreneurship education and innovation.